2022
DOI: 10.1186/s12882-022-02667-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum chromogranin A correlated with albuminuria in diabetic patients and is associated with early diabetic nephropathy

Abstract: Background The kidney is the main site for the removal of chromogranin A (CgA). Previous studies have found that patients with renal impairment displayed elevated concentrations of CgA in plasma and that CgA concentrations reflect a deterioration of renal function. In this study, we aimed to estimate serum CgA levels and to evaluate the role of serum CgA in the early diagnosis of diabetic nephropathy (DN). Methods A total of 219 patients with type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…A cutoff level of 3.46 ng/ml CgA showed 69.86% sensitivity and 66.12% specificity to detect DN in the early stage. 17 Their results were in line with our findings that showed higher serum CgA levels with deteriorating renal functions. Limitations of study: Financial constrains, small sample size and limited resources with no genetic workup added to our limitations.…”
Section: Discussionsupporting
confidence: 91%
“…A cutoff level of 3.46 ng/ml CgA showed 69.86% sensitivity and 66.12% specificity to detect DN in the early stage. 17 Their results were in line with our findings that showed higher serum CgA levels with deteriorating renal functions. Limitations of study: Financial constrains, small sample size and limited resources with no genetic workup added to our limitations.…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, the plant extract showed restorative properties of ALT, ALP, total bilirubin and AST [ 30 ]. As a result of diabetes, a raise in serum creatinine and urea was seen, which were considered major indicators of renal impairment [ 31 ]. A result from anti-diabetic research of Carduus acicularis and Cirsium maackii was consistent with our results [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also anticipated that up to 700 million people worldwide could have DR by 2045 15 . Thus, researchers have attempted to establish novel diagnostic and prognostic parameters for predicting the onset of DM and its complications in the early phase 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…15 Thus, researchers have attempted to establish novel diagnostic and prognostic parameters for predicting the onset of DM and its complications in the early phase. 16,17 Different metabolic organs communicate through the neuronal and hormonal media in different physiologic and pathologic conditions. 18 Among these, adipose-immune-pancreatic cell crosstalk is an essential pathway in the pathogenesis of diabetes and other metabolic disorders.…”
mentioning
confidence: 99%